Knowledge, attitudes and practices regarding head lice infestations in rural Nigeria - Jorg Heukelbach; Uade Samuel Ugbomoiko (Journal of Infection in Developing Countries)
Introduction: Head lice infestations are common in sub-Saharan Africa, but knowledge, attitudes and practices have never been studied in this region.